Gamifikasi sebagai Inovasi Pedagogis dalam Ilmu Shorof: Menuju Model Pembelajaran Transformatif - Abdul Ghofur; Ariga Bahrodin; Siti Durotun Naseha; Immas Anggung Mestuti Kaprawiran; Rizki Fitra Rahman; Ittaqi Haitsumakunti; Abdullah Syamil Imanuddin; Roudhotul Jannah (Fakultas Agama Islam, 2026)
Arabic morphology (Ilmu Shorof) learning in higher education is often perceived as abstract and cognitively demanding, which can reduce students’ motivation and engagement. This condition highlights the need for pedagogical innovation that enhances the quality of learning experiences. This study aims to refine a gamified learning product for Ilmu Shorof and to evaluate students’ perceptions of its pedagogical quality using the ARCS motivational model (Attention, Relevance, Confidence, Satisfaction). The research employed an evaluative approach with a descriptive quantitative design. The participants were 50 students of the Arabic Language Education program who used the refined gamification product in Ilmu Shorof learning. Data were collected through an ARCS-based perception questionnaire and analyzed using descriptive statistics. The findings indicate that gamified Ilmu Shorof learning received positive responses across all ARCS dimensions, with mean scores in the good category. These results suggest that gamification not only enhances learning motivation but also functions as a pedagogical innovation that supports a more transformative approach to Ilmu Shorof learning in higher education.